THE EFFECT OF SALARIES AND HEALTH FACILITIES ON EMPLOYEE LOYALTY OF PT BINA INSAN KAMIL INDONESIA EAST JAKARTA - Dwi Febia Ningrum; Robert Siregar; Sugeng Supriono (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This research was conducted at PT. Bina Insan Kamil Indonesia, East Jakarta. The purpose of this study is to determine the effect of salary on employee loyalty, the effect of salary on health facilities, and the effect of health facilities on employee loyalty of PT. Bina Insan Kamil Indonesia, East Jakarta. In this study, the salary and health facilities as independent variables (X), while employee loyalty is the dependent variable (Y). The problems in this research are the inadequate salary provision, inadequate health facilities, and lack of employee loyalty to the company. The population and research sample were taken as many as 60 respondents. Data analysis techniques are processed with the outer model and inner model through the SmartPLS version 3.0 application. The calculation results obtained that health facilities has a significant effect on employee loyalty of PT. Bina Insan Kamil Indonesia amounted to 2,323 T-Statistic test results, salary has a significant effect on health facilities amounting to 225,574 T-Statistic test results, while salary does not have a significant effect on employee loyalty as shown by 1,823 T-Statistic test results.